PRINCIPLES OF MANAGEMENT OF SOFT TISSUE INJURIES IN SPORTS - K. R, Lokesha; P. S, Sandhyarani; P, Bhaskar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Sports injuries are commonly caused by overuse, direct impact, or the application of force that is greater than the body part can structurally withstand. Soft tissue injuries typically describe damage to muscles, tendons, and ligaments. They may lead to pain, swelling, and restricted mobility and can occur for many reasons. Soft tissue injury may include injury to tendons, ligaments, capsules, synovium, articular cartilage and fascias. Some potential causes include athletes repeatedly overusing their soft tissues and physical trauma. Many people experience soft tissue injuries when they don’t let their muscles fully recover from a workout and continue the routine with increased intensity. Resulting from this pattern, the muscles used can experience trauma or strain. Initial treatment includes stopping the activity that caused the fracture, elevation, ice, and anti-inflammatory medicine. Continued treatment includes rest, decreasing weight-bearing on the affected area, shoe inserts or braces, and possibly cast immobilization. This article explores the types, symptoms, causes, and diagnosis of soft tissue injuries and how to treat and prevent them.